An Overview of the Importance of Conformational Flexibility in Gene Regulation by the Transcription Factors. (11th January 2010) - Khan, Shagufta H.; Kumar, Raj
Abstract : A number of proteins with intrinsically disordered (ID) regions/domains are reported to be found disproportionately higher in transcription factors. Available evidences suggest that presence of ID region/domain within a transcription factor plays an important role in its biological functions. These ID sequences provide large flexible surfaces that can allow them to make more efficient physical and functional interactions with their target partners. Since transcription factors regulate expression of target genes by interacting with specific coregulatory proteins, these ID regions/domains can be used as a platform for such large macromolecular interactions, and may represent a mechanism for regulation of cellular processes. The precise structural basis for the function of these ID regions/domains of the transcription factors remains to be determined. In the recent years there has been growing evidence suggesting that an induced fit-like process leads to imposition of folded functional structure in these ID domains on which large multiprotein complexes are built. These multiprotein complexes may eventually dictate the final outcome of the gene regulation by the transcription factors.